The results of variety test of berry crops in conditions of Republic of Komi - N. N. Sokerina (Аграрная наука Евро-Северо-Востока, 2017)
Deficiency of vitamins in northerners can be replenished by the inclusion in the diet of fruits of berry crops, the prospects of which cultivation in the Republic of Komi is due to the compliance of biological features to the climate of the region. Obtaining of high yields of berry crops is possible with the right selection of varieties. The purpose of this work was the study of varieties of berry crops on a set of basic economic-useful traits (winter resistance, productivity, quality of berries, resistance to diseases and pests) and the selection of promising varieties for the formation of adaptive agrophytocenoses of berry crops in conditions of the Republic of Komi. The research was conducted in the nursery of the FGBNU NIISKh of the Republic of Komi (Syktyvkar). The results of the long-term (2005.2016) varietal study of 107 varieties of berry crops are presented. For the formation of adaptive agrophytocenoses of berry crops in conditions of the Republic of Komi, highly productive varieties of different maturation periods are selected: black currant Lentyay, Vernost, Valovaya, Orlovskiy vals, and Arkadiya with a productivity of 4.52.5.40 kg/bush (the Orlovskiy vals was characterized by stable productivity); red currant Vika and Marmeladnitsa with a productivity of 5.84.6.02 kg/bush (stable productivity is noted in the variety Marmeladnitsa); gooseberry Mayak, Plodorodny zeleny with a productivity of 7.84.7.97 kg/bush (stable productivity was observed in the Plodorodny zeleny variety); blue honeysuckle Morena and Amfora with a productivity of 1.99.2.20 kg/bush; garden strawberry Vityaz, Kokinskaya zarya with a productivity of 1.47.1.65 kg/m; raspberry Ottava, Volnitsa with a stable productivity of 2.70.2.86 kg/m. The offered varieties provided an increase in the productivity of agrophytocenoses of berry crops in conditions of the Republic of Komi by 7.0.86.4%.